Judicial review of legislation in Canada - Strayer, Barry L. (Heritage., 1968)
This book is a systematic study of constitutional legislation in Canada in relation to constitutional development. In deciding whether legislation in the Canadian courts is constitutionally valid or invalid, the author discusses the history, theory, special problems, and rules relating to the function of the courts.